Self-propelled Subsurface Radar Detector of Low-Depth Objects - I. Yu. Malevich; A. S. Lopatchenko; T. V. Shukevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
Portable, mobile and mobile subsurface radar detectors are in high needed for localizing inhomogeneities and hidden defects in monitoring the condition of road surfaces, studying the upper layer of the earth's surface during humanitarian demining and identifying caches. Despite the presence of a number of specialized devices, the problem of ensuring reliable operational detection of near-surface and shallow objects has not been fully resolved. One of the promising directions in the development of a subsurface radar detector with an increased efficiency of object detection when deepening up to 1,5 ... 2 λ is associated with the use of a continuous ultra-wideband FMCW signal and optimization of the structural design of the system, which ensures the maintenance of a given height of rise of the antenna unit above the studied environment with its high mobility. The article presents the results of the development of a self-propelled subsurface radar detector with a continuous probing signal, including the substantiation of the technical appearance of the device, the development of a concept layout and the results of experimental studies. The device is made on a four-wheeled automated platform with an adjustable console on which the antenna unit moves. With the forward movement of the platform, a sequential radar survey of the upper soil layer is performed, the results of which in the form of a surface projection of the normalized power of depth portraits are displayed on the monitor screen. The conducted field tests of the device showed reliable detection of near- and subsurface objects made of dielectric and metallic materials.